Isolation of a morphinan alkaloid and a methoxybenzoic acid with the investigation on the antibacterial effect of alphonsea cylindrica king leaves - Tan, Siow-Ping (Tanjung Malim, 2021)
Isolation of a morphinan alkaloid and a methoxybenzoic acid with the investigation on the antibacterial effect of alphonsea cylindrica king leaves by Tan, Siow-Ping